NOTES ON THE DISTRIBUTION OF RED ALGAE (RHODOPHYTA) ON THE CORAL REEF OF PARI ISLANDS, SERIBU ISLANDS - Atmadja, Wanda Surjana (Marine Research in Indonesia, 1977)
Many species of red algae are economically important for their carrageenan contents. Since May 1974 to June 1975 an intensive survey on their distributions have been carried out on the fringing reef of Pari Islands, Seribu Islands. Thirty five species of Rhodophyta have been identified and their species composition and relative importance as compared to Phaeophyta and Chlorophyta have been studied. Environmental factors, such as bottom type and seasonal influence on their distribution, emphasized in the discussion. Further studies on inventory and the distribution of these algae will be continued particularly in support of the culture experiments for some of the species.